A CONTENT ANALYSIS OF GOVERNMENT ENGLISH TEXTBOOK FOR THE SECOND SEMESTER STUDENTS OF GRADE TEN OF SENIOR HIGH SCHOOLS: A CRITICAL LOOK ON ITS SUITABILITY TO CRITERIA OF MATERIAL DEVELOPMENT AND 2013 CURRICULUM - ., SARI DEWI NOVIYANTI; ., PROF. DR. I KETUT SEKEN, M.A.; ., DRS. I WAYAN SUARNAJAYA, M.A., P.hD (Jurnal Pendidikan Bahasa Inggris Indonesia, 2015)
Penelitian ini bertujuan untuk menganalisis kesesuaian buku bahasa inggris dengan kriteria penyusunan materi ajar dan kurikulum 2013. Analisis kesesuaian buku teks dengan riteria penyusunan materi ajar berdasarkan pada beberapa kriteria yaitu; kemasan, latar dan desain, tugas dan kegiatan, kecakapan, bahasa dan isi, dan subjek dan isi, sedangkan analisis kesesuaian pada kurikulum 2013 berdasarkan pada tujuan, isi, model pembelajaran dan tahapan pembelajaran, dan evaluasi. Analisis konten pada teks secara kualitatif merupakan metode penelitian dan buku bahasa inggris kurikulum 2013 merupakan data penelitian. Data diperoleh berdasarkan observasi buku teks dan analisis secara kuantitatif dan kualitatif. Temuan menunjukkan bahwa: kesesuaian buku teks dengan kriteria penyusunan materi ajar pada kemasan yaitu 54% dari 13 sub kriteria, 62% dari 8 sub kriteria untuk latar dan desain, 100% dari 4 sub kriteria untuk tugas dan kegiatan, 83% dari 6 sub kriteria untuk kecakapan, 75% dari 4 sub kriteria untuk bahasa dan isi, dan 100% dari 3 sub kriteria untuk subjek dan isi. Sedangkan untuk kesesuaian dengan kurikulum 2013, kesesuaian buku teks mencapai 100% dari 2 sub kategori untuk isi, 100% dari 8 sub kategori untuk konten, 75% dari 4 sub kriteria untuk model pembeajaran dan tahapan pembelajaran, dan 100% dari 3 sub kriteria untuk evaluasi. Secara kualitatif, ditemukan beberapa kelemahan pada buku teks seperti tidak adanya informasi yang lengkap tentang penerbit dan penulis buku, tidak adanya kegiatan keterampilan mendengar, tidak adanya penjelasan pendahuluan untuk topik, struktur teks dan tata bahasa, kurangnya penggunaan materi otentik, kurangnya penekanan nilai karakter, tidak adanya penggunaan pembelajaran model proyek, dan kurangnya penialain terhadap sikap. Implikasi penelitian ini adalah buku teks ajar seharusnya disusun berdasarkan dua kriteria yaitu kriteria penyusunan materi ajar dan kurikulum 2013 agar tujuan peningkatan kemampuan komunikasi siswa dapat tercapai sebagaimana tercantum dalam tujuan kurikulum nasional.Kata Kunci : buku teks, kriteria penyusunan materi ajar, kurikulum 2013 This study aimed at analyzing the suitability of English textbook to criteria of material development and 2013 Curriculum. Criteria of material development analysis was based on several criteria, namely: package, layout and design, task and activities, skills, language and content and subject and content, while the analysis of 2013 Curriculum was based on the objectives, content, learning model and phases and evaluation. Discourse Qualitative Content Analysis was the research method and 2013 Curriculum based English textbook was the data corpus. Data were gathered through textbook observation and were analyzed quantitatively and qualitatively. Findings showed that: the textbook suit the criteria of material development for 54% of package from 13 subsections, 62% of layout and design from 8 subsections, 100% of task and activities from4 subsections, 83% of skills from 6 subsections, 75% of language and content from 4 subsections, and 100% of subject and content from 3 subsections, and final result showed that the level suitability of the textbook to criteria of material development is 3.95 which is categorized as good suitability. While for textbook suitability to 2013 curriculum, the textbook suit the 2013 curriculum for 100% of objectives from 2 subsections, 100% of content from 8 subsections, 75% of learning model and phases from 4 subsections, and 100% for the evaluation from 3 subsections and final result showed that the level suitability of the textbook to 2013 Curriculum is 4.7 which is categorized as very good suitability. Qualitatively, several weaknesses were found in the textbook such as insufficient information of publisher and authors, lack of listening activities, no overview of topic, structure and grammar, less authentic material, insufficient character education discussed, no project based learning model and insufficient amount of attitude evaluation. The implication of this study that a textbook should be developed in consideration of criteria of standard material development and curriculum applied especially to make a published textbook has good quality to build up students’ communicative skill can be achieved successfully as stated in the objectives of the national curriculum.keyword : textbook, criteria of material development, 2013 curriculum